Accelerated epigenetic aging in Down syndrome - Horvath, Steve; Garagnani, Paolo; Bacalini, Maria Giulia; Pirazzini, Chiara; Salvioli, Stefano; Gentilini, Davide; Di Blasio, Anna Maria; Giuliani, Cristina; Tung, Spencer; Vinters, Harry V.; Franceschi, Claudio (Aging cell, 2015)
Summary Down Syndrome (DS) entails an increased risk of many chronic diseases that are typically associated with older age. The clinical manifestations of accelerated aging suggest that trisomy 21 increases the biological age of tissues, but molecular evidence for this hypothesis has been sparse. Here, we utilize a quantitative molecular marker of aging (known as the epigenetic clock) to demonstrate that trisomy 21 significantly increases the age of blood and brain tissue (on average by 6.6 years, P = 7.0 × 10−14).